Credit Supply and Rice Output in Nigeria: Empirical Insight from Vector Error Correction Model Approach - Omoregie, Osaretin Kayode; Ikpesu, Fredrick; Okpe, Abraham Emmanuel (International Journal of Economics and Financial Issues, 2018)
This study investigated the effect of credit supply on rice output in Nigeria within the periods 1981 to 2016 by employing the VECM approach. Findings from the research revealed that a rise in credit supply would lead to increase in rice output. In addition, the study indicated that a shock in investment, and labour would cause decline in rice output while a shock in money supply and inflation rate would cause rice output to rise in the country. Based on the result of the study, it is recommended that government in partnership with deposit money banks should create a scheme that will provide an interest free loan to farmers that are involved in rice production. Also, government should encourage rice farmers by supplying them farm inputs (which includes the provision of high yielding varieties, fertilizers, land, irrigation) at a subsidizes rate. Keywords: Credit Supply, Rice Output, VECM JEL Classifications: C5, Q1, Q14